The DELAYED ABAXIAL TRICHOMES Helitron has dual functions in vegetative and pollen development in Arabidopsis thaliana - Erin Doody; Jianfei Zhao; Bishwas Sharma; R. Scott Poethig (Proceedings of the National Academy of Sciences, 2026)
Transposons drive genetic diversity and evolution by altering the genomic landscape over time. Here, we describe D ELAYED AB AXIAL TRICHOMES ( DAB ), a Helitron/RC transposable element in Arabidopsis thaliana that has a role in vegetative phase change and gametogenesis. A genome-wide association study (GWAS) for the timing of abaxial trichome development (an adult leaf trait) in A. thaliana revealed a conserved haplotype of polymorphisms within DAB that delays abaxial trichome production. CRISPR-Cas9-induced deletions of DAB are gametophytic pollen-lethal, indicating that this locus is also required for pollen production. DAB produces 24-nucleotide siRNAs with sequence complementarity to genes involved in embryogenesis, gametogenesis, and seed development. DAB also impacts the expression of ARGONAUTE genes, genes involved in RNA-directed DNA methylation (RdDM), as well as genes in several key genetic pathways. This global effect on gene expression suggests that DAB may have functions beyond those identified in this study.